A location-inventory model considering a strategy to mitigate disruption risk in supply chain by substitutable products. (June 2017) - Farahani, Maryam; Shavandi, Hassan; Rahmani, Donya
Highlights: Developing a multiple product inventory location problem in supply chain under disruption. Considering partially disruption of centers and substitutable products as a strategy to reduce the risk of disruption. Developing a hybrid solution algorithm, TS-VNS. Abstract: In this paper we consider a multiple products inventory location problem with disruption. Disruptions may occur in any supply chain due to several reasons such as earthquakes, floods, fires, labor strikes, terrorist attacks, equipment breakdowns and economic crises. We develop a model by assuming that facilities may fail partially in case of disruption and considering substitutable products as a strategy to mitigate the risk of disruption. The developed model is a non-linear integer programming model and NP-Hard. To solve the model, a hybrid algorithm including Tabu Search (TS) and Variable Neighborhood Search (VNS) is proposed. Numerical results show reasonable performance of the algorithm and signify the importance of multiple substitutable products strategy to manage arising disruptions. Finally, conclusion and future researches are presented.